Simultaneous recovery and quantitative determination of Cu, Co, Ni, Cr and V in public drinking water quality assessment - Alias Mohd. Yusof, 1951-2014; Lee, P. S.; Abdul Khalik Wood; International Nuclear Conference (2002 : Kuala Lumpur) (Skudai : Universiti Teknologi Malaysia, 2002)
10